Touching to Feel: Brain Activity During In-Store Consumer Experience - Balconi, Michela; Venturella, Irene; Sebastiani, Roberta; Angioletti, Laura (Frontiers in Psychology, 2021)
To gain a deeper understanding of consumers’ brain responses during a real-time in-store exploration could help retailers to get much closer to costumers’ experience. To our knowledge, this is the first time the specific role of touch has been investigated by means of a neuroscientific approach during consumer in-store experience, within the field of sensory marketing. This study explores the presence of distinct cortical brain oscillations in consumers’ brain while navigating a store, that provides a high-level of sensory arousal, and being allowed or not to touch products. A 16-channel wireless electroencephalogram (EEG) was applied to 23 healthy participants (Mage = 24,57 SD = 3,54), with the interest in cosmetics but naïve about the store explored. Subjects were assigned to two experimental conditions based on the chance of touching or not touching the products. Cortical oscillations were explored by means of power spectral analysis of the following frequency bands: delta, theta, alpha, beta. Results highlighted the presence of delta, theta, and beta bands within the frontal brain regions during both sensory conditions. The absence of touch was experienced as a lack of perception that needs cognitive control, as reflected by Delta and Theta band left activation, whereas a right increase of Beta band for touch condition was associated to sustained awareness on the sensory experience. Overall, EEG cortical oscillations functional meaning could help to highlight the neurophysiological implicit responses to tactile conditions and the importance of touch integration in consumers’ experience.